Experimental purification of paclitaxel from a complex mixture of taxanes using a simulated moving bed - Cremasco,M. A. (2009)
A laboratory-scale simulated moving bed (SMB) was designed and tested for the separation of paclitaxel, a powerful anti-cancer agent known as Taxol@, from impurities of a plant tissue culture (PTC) broth. The innovative strategy of a pseudo-binary model, where mixtures A and B were treated as single solutes A and B, was used in the linear standing wave analysis to fix the SMB operating parameters for a multicomponent and complex system. Linear standing wave design was used to specify the zone flow rates and the switching time for the laboratory-scale SMB unit, with two steps of separation. The SMB consists of four packed columns, where each column is 12.5 cm in length and 1.5 cm in diameter. Two sequential separation steps were used to recover paclitaxel from a small feed batch (less than one liter). Placlitaxel was recovered from the complex plant tissue culture broth in 82% yield and 72% purity.